Examining the mediating role of innovative organizational culture between transformational leadership styles and organizational commitment - Alshuhumi, Said Rashid Ali; Al-Hidabi, Dawood Abdulmalek Yahya; Akinbode, Akintola Ismaila (Frontiers, 2025)
This study investigates the impact of transformational leadership (TL) on organizational commitment (OC) and examines the mediating role of innovative organizational culture (IOC) among Omani primary school teachers. A crosssectional quantitative design was employed, collecting data from 368 teachers using validated surveys. Structural Equation Modeling (SEM) was conducted to test the hypothesized relationships. Results indicate that individualized consideration (β = 0.816, p < 0.001) and inspirational motivation (β = 0.934, p < 0.001) positively and significantly predict all dimensions of organizational commitment, whereas idealized influence (β = −0.165, p = 0.001) and intellectual stimulation (β = −1.629, p < 0.001) show negative effects. Organizational culture significantly influences commitment, with the strongest effect observed on normative commitment (β = 0.708, p < 0.001). Furthermore, IOC mediates the TL–OC relationship, with a significant indirect effect of β = 0.573 (p < 0.001), suggesting that a supportive organizational culture enhances the effectiveness of transformational leadership on teacher commitment. The findings underscore the need for the Ministry of Education to invest in leadership development programs emphasizing transformational leadership and for school leaders to foster an innovative, collaborative culture to strengthen teacher commitment, improve student outcomes, and enhance overall school performance.